A year of transient tracers (chlorofluorocarbon 12 and sulfur hexafluoride), noble gases (helium and neon), and tritium in the Arctic Ocean from the MOSAiC expedition (2019–2020) - Heuzé, Céline; Huhn, Oliver; Walter, Maren; Sukhikh, Natalia; Karam, Salar; Körtke, Wiebke; Vredenborg, Myriel; Bulsiewicz, Klaus; Sültenfuß, Jürgen; Fang, Ying-Chih; Mertens, Christian; Rabe, Benjamin; et al. (Earth System Science Data, 2023)
Abstract. Trace gases have demonstrated their strength for oceanographic studies, with applications ranging from the tracking of glacial meltwater plumes to estimates of the abyssal overturning duration. Yet measurements of such passive tracers in the ice-covered Arctic Ocean are sparse. We here present a unique data set of trace gases collected during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition, during which R/V Polarstern drifted along with the Arctic sea ice from the Laptev Sea to Fram Strait, from October 2019 to September 2020. During the expedition, trace gases from anthropogenic origin (chlorofluorocarbon 12 (CFC-12), sulfur hexafluoride (SF6), and tritium) along with noble gases (helium and neon) and their isotopes were collected at a weekly or higher temporal resolution throughout the entire water column (and occasionally in the snow) from the ship and from the ice. We describe the sampling procedures along with their challenges, the analysis methods, and the data sets, and we present case studies in the central Arctic Ocean and Fram Strait to illustrate possible usage for the data along with their robustness. Combined with simultaneous hydrographic measurements, these trace gas data sets can be used for process studies and water mass tracing throughout the Arctic in subsequent analyses. The two data sets can be downloaded via PANGAEA: https://doi.org/10.1594/PANGAEA.961729 (Huhn et al., 2023a) and https://doi.org/10.1594/PANGAEA.961738 (Huhn et al., 2023b).